Respuesta :

Step-by-step explanation:

Question 46.

[tex](2\sqrt{5}-\sqrt{2} )^2=(2\sqrt{5})^2-2*2\sqrt{5}*\sqrt{2} +(\sqrt{2})^2 } =4*5-4*\sqrt{2*5} +2=\\=20-4\sqrt{10}+2=22-4\sqrt{10}.[/tex]

Answer: E. None of these.

Question 47.

[tex]\frac{4\sqrt{5} }{\sqrt{3} } =\frac{4*\sqrt{5}*\sqrt{3} }{\sqrt{3} *\sqrt{3} } =\frac{4*\sqrt{5*3} }{3}=\frac{4\sqrt{15} }{3} .[/tex]

Answer: E. None of these.

Answer:

45) E 47) E

Step-by-step explanation:

45)

Remember the formula [tex](a-b)^2=a^2-2ab+b^2[/tex]

[tex](2\sqrt5-\sqrt2)^2=(2\sqrt5)^2-2(2\sqrt5\times\sqrt2)+(\sqrt2)^2\\\\=20-2(2\sqrt{10})+4\\\\=24-4\sqrt{10}[/tex]

Hence E. None of these.

47)

[tex]\frac{4\sqrt{5}}{\sqrt3}=\frac{4\sqrt5\times\sqrt3}{\sqrt3\times\sqrt3}\\\\=\frac{4\sqrt15}{3}[/tex]

Hence E. None of these.

Have a nice day, also please mark brainliest thanks :)